Círculos de contação de histórias infantis e os processos de auto/(trans)formação permanente das educadoras no ser/fazer pedagógico - Hundertmarck, Nilta de Fátima (2014)
This research report resulted in a Master's thesis in Education, developed in Training, Knowledge and the Professional Development line. It has been aimed to investigate the repercussions of storytelling circles for children in the processes of self-permanent (trans) formation of educators in their pedagogical being/doing practice. This research is qualitative in nature, the educators type, with a hermeneutic approach, there will be interpreted narratives of storyteller teachers of children's stories that are part of the Group "Story Time: girls and boys reading the world and the word" of the Federal University of Santa Maria/RS. The research´s subjects are four educators teaching students in the early years and working in schools. To scroll through different views of the world, I chose as theoretical support the boy who learned to read the world, scratching the ground with sticks, Paulo Freire, who will talk over the texts with other authors as Imbernón, Bussato, Arroyo, Coelho. In data analysis it was sought to make a dialogue with several authors, with the intertwining narratives of educators counting some children's stories or worked in storytelling circles. From the principles of dialog and lovingness that both defended and experienced in education, Freire urges us to (re) create, (re) invent (re) discover ways to (re) telling children and (re) enchant our life story, seeking to reduce the distance that separates our pedagogical being towards a (trans) formative school as a place to be happy. The Tale of the Time Group: boys and girls reading the word and the world, through the circles of storytelling enables moments of experience, allowing educators/storytellers talk about their life stories, children's stories, establishing dialogues about their educational practices, contributing to realize that there are gaps regarding the absence of telling children stories or how they happen to be in pedagogical being/doing practice. The dialogical-reflective spaces and the proposals led from the meetings in/with the group moved to curiosities about the practice of these teachers, (re) creating attitudes toward storytelling.